2017
DOI: 10.1159/000481229
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of 18-mm-Diameter Colonic Stents for Obstructive Colorectal Cancers

Abstract: Objectives: This study aimed to evaluate the characteristics and the feasibility of 18-mm-diameter stents for obstructive colorectal cancer, comparing the clinical courses with 22- mm-diameter stents. Methods: We retrospectively compared 33 consecutive cases treated with 18-mm-diameter stents (bridge to surgery [BTS] in 25, palliative therapy [PAL] in 8) with 27 consecutive cases treated with 22-mm-diameter stents (BTS in 21, PAL in 6) for obstructive colorectal cancer between May 2013 and November 2015 in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Comparisons of SEMSs with several diameters did not show any differences in technical success, clinical success, or adverse events including perforation [22, 76 -79]. Smallercaliber stents were considered to produce less mechanical stress, with a potentially decreased perforation rate [76,79]. However, a few studies have suggested an association between small-diameter stents (< 24 mm) and adverse events, in particular stent migration [21, 80 -82].…”
Section: Recommendationmentioning
confidence: 99%
“…Comparisons of SEMSs with several diameters did not show any differences in technical success, clinical success, or adverse events including perforation [22, 76 -79]. Smallercaliber stents were considered to produce less mechanical stress, with a potentially decreased perforation rate [76,79]. However, a few studies have suggested an association between small-diameter stents (< 24 mm) and adverse events, in particular stent migration [21, 80 -82].…”
Section: Recommendationmentioning
confidence: 99%
“…These devices are capable of holding tissue around the endoscope but not the tissue away from it. Large size stents were clinically tested for the treatment of obstructive colorectal cancers [7]. However, the mesh of stents is normally fine and performing surgical tasks in between the mesh is not realistic.…”
Section: Introductionmentioning
confidence: 99%
“…Small diameter stents mitigate the mechanical impact of the stents on the tumor and the colonic wall, and can reduce the perforation rate. Ogawa et al [7] found that the 18-mm diameter stents were effective similar to 22-mm diameter stents. Because 18-mm diameter stents are easy to handle and produce less mechanical stress, they have the potential to decrease the perforation rate and mitigate the stent's impact on the tumors.…”
mentioning
confidence: 96%